ASAS RETROAKTIF DALAM PERSPEKTIF HUKUM ISLAM (Syiar Hukum, 2010)
The application of Criminal Law is based on the principle of legality.Â  As a result, a person may not be prosecuted under Criminal Law that has not been previouslyÂ  published.Â  However, Act Number 26 of 2000 on Human Rights Trial recognises the application of the principle of retroactivity to an act which is classified as a gross violation against human rights. This paper will examine the principle of retroactivity under Islamic Law.Â  According to Islamic Law, the principle of retroactivity may be applied if it is based on the principle of justice and public order, and in establishing public order it should be accordance with the rules and spirit of syariâah.Â  The writer is of the opinion that for resolving a serious crime or violence in the past, it is better to use reconciliation approach as the application of the principle of retroactivity to crimes in past will have difficulties in finding legal evidence